Relationships Between Nutrient Of Land And Cow’s Blood Added With Bioactivators On Performance of Soybean (Glycine max (L.) Merr.) - Podesta, Fiana; Harini, Ririn; Fitriani, Dwi; Suryadi, Suryadi (Akta Agrosia, 2020)
Soybean production in Bengkulu Province is still lower than national production. Soybean production can still be improved by adding nutrients, one source of untapped nutrients is cow's blood which is still a waste. The purpose of this research is to determine the effect of cow’s blood added with bioactivators on growth performance of soybean. This research was conducted by using a complete randomized design (CRD) arranged factorially consisted of two factors with three replications. The first factor was the various kinds of cow’s blood added with bioactivators consisting of Yeast, Stale Rice, Microorganism-Bio(M-Bio), Effective Microorganism-4 (EM-4), and Rumen. The second factor was the concentration of cow’s blood added with bioactivators consisting of 15%, 30%, and 45%. Results showed: 1) There was no treatments interaction between various kinds of cow’s blood added with bioactivators and its concentration in the growth, 2) the various kinds of cow’s blood added with  bioactivators had significant effect in the growth of plant height, number of leaves, number of branches, wet and dry weight, but it had no significant effect on plant height and leaf area, and 3) The concentration of cow’s blood added with bioactivators  has no significant effect in the growth.  This study indicated that cow’s blood added with Rumen as bioactivator showed better growth performance of soybean. Keywords: bioactivators, cow’s blood, nutrient of land, performance of soybean